Endoscopic Resection for Superficial Non-Ampullary Duodenal Epithelial Tumors - Hye Kyung Jeon; Gwang Ha Kim (Gut and Liver)
An increasing number of superficial non-ampullary duodenal epithelial tumors (SNADETs) have been detected recently owing to the development of endoscopic imaging technology and increased awareness of this disease. Endoscopic resection is the first-line treatment for SNADETs, with methods including cold snare polypectomy (CSP), conventional endoscopic mucosal resection (cEMR), underwater EMR (uEMR), and endoscopic submucosal dissection (ESD). Here, we review the current status and recent advances in endoscopic resection for SNADETs. Endoscopic resection in the duodenum is more difficult and has a higher risk of adverse events than that in other organs owing to specific anatomical disadvantages. SNADETs ≤10 mm in size are candidates for CSP, cEMR, and uEMR. Among these lesions, suspected carcinoma lesions should not be treated using CSP because of their low curability. cEMR or uEMR is considered for lesions sized 10 to 20 mm, whereas piecemeal EMR or ESD is considered for tumors >20 mm in size. In particular, ESD or surgical resection should be considered for suspected carcinoma lesions >30 mm in size. The treatment plan should be selected on a case-to-case basis, considering the balance between the risk of adverse events and the necessity of en bloc resection.